Classical Sufi Axiology as a Methodological Resource for Contemporary Family Studies: A Phenomenological-Hermeneutic Analysis - Gafurov Doniyor Orifovich (Researchparks Publishing, 2026)
This article presents a systematic phenomenological-hermeneutic analysis of classical Sufi axiology as a methodological resource for contemporary family studies. Against the backdrop of postmodern axiological turbulence and the destabilization of family institutions globally, the study explores how the integral conceptual paradigm of classical Sufi tariqats — encompassing the teachings of al-Ghazali, Rumi, Ibn Arabi, Naqshband, Yasawi, Kubra, and Makhdumi Azam — offers epistemologically valuable insights for modern family research. The investigation employs a triangulated methodology combining hermeneutic textual analysis of primary Sufi sources, comparative-conceptual analysis with Western phenomenological axiology (Scheler, Hartmann), and integrative-synthetic mapping with contemporary family theories (Gottman, Sternberg, Bowlby, Bronfenbrenner). The findings demonstrate that classical Sufi axiology operates through three interconnected dimensions — onto-metaphysical, gnoseological-irfani, and ethopoetico-praxiological — which collectively constitute a multilayered architecture for family well-being. The study identifies seven core axiological constants (love, patience, forgiveness, respect, mercy, fidelity, halal sustenance) that exhibit paradigmatic correspondence with empirically validated predictors in modern family psychology. The discussion argues that the conceptual synthesis of classical Sufi heritage and contemporary family studies provides a genuine theoretical contribution to global family scholarship, particularly relevant for post-Soviet Central Asian contexts. Theoretical implications include the development of a culturally embedded family well-being framework that transcends the limitations of secular individualistic models. Practical implications encompass applications in family counseling, premarital education programs, and parental responsibility training. The article concludes that classical Sufi axiology represents not merely an archaeological-historical resource but a vital epistemological framework for addressing contemporary family crises.